Immunization Coverage Assessment And K.A.P Study In Gwalior District - Govila A.K; Chaurasia A.R; Jain V.K; Dixit A.K; Agarwal P.L; Mahajan P.C; Bhagwat A.K; Sapra S; Bhatnagar D.P (Wolters Kluwer Medknow Publications, 1986)
An evaluation of Immunization coverage and K.A.P study in District Gwalior was under taken by the Deptt. Of community Medicine, G.R. Medical college, Gwalior involving Medical Interns and students. Thirty cluster technique as recommended by W.H.O was used for the assessment. Results showed a good coverage in immunization of pregnant women and children of Gwalior district. However, the dropout rates between the 1st and the remaining dose were quite high. An analysis of KA.P of parents of children revealed that ignorance was the main factor for improper coverage and dropouts which may be augmented by I.E.C. activities in the District Gwalior.